Ethnicity and the prostate cancer experience: a qualitative metasynthesis. Issue 10 (23rd August 2016) - Rivas, Carol; Matheson, Lauren; Nayoan, Johana; Glaser, Adam; Gavin, Anna; Wright, Penny; Wagland, Richard; Watson, Eila
Abstract: Objectives: To summarize black and minority ethnic (BME) patients' and partners experiences of prostate cancer by examining the findings of existing qualitative studies. Methods: We undertook a systematic metasynthesis of qualitative studies using a modified version of Noblit and Hare's "meta‐ethnography" approach, with a 2000‐2015 search of 7 databases. Results: Thirteen studies of men from US and UK BME groups were included. We explored constructs with BME‐specific features. Health care provider relationships, formation of a spiritual alliance with God (which enhanced the participants' feeling of empowerment and ability to cope with the cancer), and living on for others (generally to increase cancer awareness), often connected to spiritual regrowth, were the 3 constructs most commonly reported. A magnified effect from erectile dysfunction was also common. Initially, this affected men's disclosure to others about their cancer and their sexual problems, but eventually men responded by shifting their conceptualizations of masculinity to sustain self and social identities. There was also evidence of inequality resulting from financial constraints and adversity that necessitated resilience in coping. Conclusions: The prostate cancer experience of BME men and their partners is affected by a complex intersection of ethnicity with other factors. Health care services should acknowledge this. If providers recognize the men's felt masculinities, social identities, and spiritual beliefs and their shifting nature, services could be improved, with community as well as individual benefits. More studies are needed in diverse ethnic groups.